Rescue and Firefighting Operations During Incidents Involving Alternatively Powered Vehicles. Gas Propulsion - Kielin, Jan; Zboina, Jacek; Bugaj, Grzegorz; Zalech, Jacek; Bąk, Damian (Safety & Fire Technology, 2023)
Aim: The purpose of this article is to present the most important information and conclusions about gas-powered motor vehicles and the associated risks during fires and local emergencies. An additional area of consideration for the article’s authors is the challenges that emergency services may encounter during rescue and firefighting operations involving such vehicles. Introduction: Technological advances in propulsion systems used in vehicles and machinery pose a variety of challenges for fire protection. It results in the evolution of known threats and the emergence of new ones. Among other things, these developments have a significant impact on the technologies of rescue operations during fires and traffic accidents involving vehicles with different propulsion systems (increasingly using gaseous fuels). Equally important is ensuring fire safety when operating such vehicles. Methodology: On the basis of a review and analysis of the literature on the subject, as well as available research results, conclusions have been formu- lated regarding the fire safety of gas-powered vehicles. Aspects relevant to conducting rescue and firefighting operations involving such vehicles were taken into account. Conclusions: Necessary measures to improve fire protection, including the conduct of effective rescue and firefighting operations during incidents involving alternatively powered vehicles include: 1. Keeping as accurate a record as possible of fires and local emergencies involving the vehicles in question. 2. Urgently developed and updated educational materials that allow training, both for the rescuers and commanders of KSRG units, in blended learning mode, and systematically conducted such training. An example of this is the educational platform prepared by CNBOP-PIB in 2009 for OSP rescuers (rescue operations) and rural residents (handling emergency situations). The platform is still in place today, and although it needs updating, it has been used successfully for many years for training and professional development of a wide range of the rescuers. 3. A rescue database of vehicles involved in incidents urgently prepared and made available to the rescuers of firefighting units that are part of the KSRG. Such a base should be established immediately or be available on terms convenient to the rescue units (such as CRS or ERG). Keywords: alternative propulsion, CNG, LNG, methane, LPG, ethane, propane, methanol, fuel cells, emergency cards, fire safety